Alcohol Interactive Toxicity Beliefs and ART Non-adherence Among HIV-Infected Current Drinkers in Mbarara, Uganda. - Fatch, Robin; Emenyonu, Nneka; Muyindike, Winnie; Kekibiina, Allen; Woolf-King, Sarah; Hahn, Judith (AIDS & Behavior, 2017)
Interactive toxicity beliefs regarding mixing alcohol and antiretroviral therapy (ART) may influence ART adherence. HIV-infected patients in Uganda completed quarterly visits for 1 year, or one visit at 6 months, depending on study randomization. Past month ART non-adherence was less than daily or <100 % on a visual analog scale. Participants were asked if people who take alcohol should stop taking their medications (belief) and whether they occasionally stopped taking their medications in anticipation of drinking (behavior). Visits with self-reported alcohol use and ART use for ≥30 days were included. We used logistic regression to examine correlates of the interactive toxicity belief and behavior, and to determine associations with ART non-adherence. 134 participants contributed 258 study visits. The toxicity belief was endorsed at 24 %, the behavior at 15 %, and any non-adherence at 35 % of visits. In multivariable analysis, the odds of non-adherence were higher for those endorsing the toxicity behavior [adjusted odds ratio (AOR) 2.06; 95 % confidence interval (CI) 0.97-4.36] but not the toxicity belief (AOR 0.63; 95 % CI 0.32-1.26). Clear messaging about maintaining adherence, even if drinking, could benefit patients.